Are the estrogen receptor and SIRT3 axes of the mitochondrial UPR key regulators of breast cancer subtype determination according to age?. Issue 3 (6th August 2021) - Jenkins, Edmund Charles; Chattopadhyay, Mrittika; Germain, Doris
Abstract: Aging is a major risk factor of developing breast cancer. Despite the fact that postmenopausal women have lower levels of estrogen, older women have a higher rate of estrogen receptor alpha (ERα)‐positive breast cancer. Conversely, young women who have elevated levels of estrogen tend to develop ERα‐negative disease that is associated with higher rate of metastasis. This perspective proposes a unifying model centered around the importance of mitochondrial biology in cancer and aging to explain these observations. Mitochondria are essential for the survival of cancer cells and therefore pathways that maintain the functionality of the mitochondrial network in cancer cells fulfill a critical role in the survival of cancer cells. The ERα and the mitochondrial sirtuin‐3 (SIRT3) have been reported to be key players of the mitochondrial unfolded protein response (UPR mt ). The UPR mt is a complex retrograde signaling cascade that regulates the communication between the mitochondria and the nucleus to restore mitochondrial fitness in response to oxidative stress. SIRT3 is a major regulator of aging. Its level decreases with age and single‐nucleotide polymorphisms that preserve its expression at higher levels are observed in centenarians. We propose a model whereby the ERα axis of the UPR mt acts to compensate for the loss of SIRT3 observed with age, and becomes the dominant axis of the UPR mt to maintain the integrity of the mitochondria during transformation, thus explaining the selective advantage of ERα‐positive luminal cells in breast cancer arising from older women.